Digging adaptations evolved independently in two lineages of Psammophiid snake: evidence from cranial morphology. Issue 2 (28th October 2022) - Sekits, Nick; Tunnell-Wilson, Walter; Jackson, Kate
ABSTRACT: The Beaked Snakes ( Rhamphiophis ) are semi-fossorial snakes with reinforced snouts adapted for digging. The Skaapstekers ( Psammophylax) are generalist terrestrial snakes. Both belong to the family, Psammophiidae. The Striped Beaked Snake ( Kladirostratus acutus ) was originally assigned to the genus Rhamphiophis, because of its beak-like snout. However, molecular evidence indicates that K. acutus is more closely related to Psammophylax . Thus, the "beak" of K. acutus must have evolved independently of that seen in Rhamphiophis . We studied the cranial morphology of K. acutus and representatives of Psammophylax and Rhamphiophis to identify possible traits that may reflect independent derivation of a beak-shaped snout relative to Rhamphiophis . We found that K. acutus retains four main cranial features in common with the Psammophylax : (1) an open fenestra between the premaxilla, nasals and septomaxilla, (2) a lack of fusion between the septomaxilla and the vertical lamina of the nasal, (3) the conchal processes of the septomaxilla extend beyond the dorsal margin of the septomaxilla and (4) a lack of contact between the prefrontals and the dorsal laminae of the nasals. Simultaneously, K. acutus displays traits associated with adaptation to semi-fossorial life in snakes such as a shortening of the maxilla, modification of the premaxilla, elongation of the nasal region, and a narrowing of the braincase.